Identification of protein biomarkers in human serum using iTRAQ and shotgun mass spectrometry. - Koutroukides, T; Jaros, J; Amess, B; Martins-de-Souza, D; Guest, P; Rahmoune, H; Levin, Y; Deery, M; Charles, P; Hester, S; Groen, A; Christoforou, A; et al. (2013)
Blood serum is one of the easiest accessible sources of biomarkers and its proteome presents a significant parcel of immune system proteins. These proteins can provide not only biological explanation but also diagnostic and drug response answers independently of the type of disease or condition in question. Shotgun mass spectrometry has profoundly contributed to proteome analysis and is presently considered as an indispensible tool in the field of biomarker discovery. In addition, the multiplexing potential of isotopic labeling techniques such as iTRAQ can increase statistical relevance and accuracy of proteomic data through the simultaneous analysis of different biological samples. Here, we describe a complete protocol using iTRAQ in a shotgun proteomics workflow along with data analysis steps, customized for the challenges associated with the serum proteome.